2010
DOI: 10.1038/mt.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Localized Neurotrophin Gene Expression on Spiral Ganglion Neuron Resprouting in the Deafened Cochlea

Abstract: A cochlear implant may be used to electrically stimulate spiral ganglion neurons (SGNs) in people with severe sensorineural hearing loss (SNHL). However, these neurons progressively degenerate after SNHL due to loss of neurotrophins normally supplied by sensory hair cells (HCs). Experimentally, exogenous neurotrophin administration prevents SGN degeneration but can also result in abnormal resprouting of their peripheral fibers. This study aimed to create a target-derived neurotrophin source to increase neuron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(143 citation statements)
references
References 48 publications
12
129
0
Order By: Relevance
“…However, the use of osmotic pumps to deliver neurotrophic factors clearly is not a good option for clinical application, particularly due to concerns about infection Staecker et al 2010). Numerous recent studies have explored alternative strategies for cochlear delivery of neurotrophins (Hendricks et al 2008;Richardson et al 2008), including cell-based therapies (Warnecke et al 2007;Pettingill et al 2008;Wise et al 2011), hydrogels (Endo et al 2005, and gene therapy using adenovirus-mediated expression of neurotrophic factors (Nakaizumi et al 2004;Rejali et al 2007;Chikar et al 2008;Wise et al 2010). These methods may provide better alternatives in the future, but they are still under development and concerns about potential side effects and risks have not yet been adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of osmotic pumps to deliver neurotrophic factors clearly is not a good option for clinical application, particularly due to concerns about infection Staecker et al 2010). Numerous recent studies have explored alternative strategies for cochlear delivery of neurotrophins (Hendricks et al 2008;Richardson et al 2008), including cell-based therapies (Warnecke et al 2007;Pettingill et al 2008;Wise et al 2011), hydrogels (Endo et al 2005, and gene therapy using adenovirus-mediated expression of neurotrophic factors (Nakaizumi et al 2004;Rejali et al 2007;Chikar et al 2008;Wise et al 2010). These methods may provide better alternatives in the future, but they are still under development and concerns about potential side effects and risks have not yet been adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the latter study also used immunohistochemical techniques to demonstrate that both the fibers in the osseous spiral lamina and ectopic sprouting fibers were afferent peripheral processes of SG neurons. Interesting recent work has shown that adenoviralmediated expression of BDNF in the cochlea, presumably eliciting much lower concentrations of neurotrophin, also can induce radial nerve fiber regrowth (Shibata et al 2010;Wise et al 2010).…”
Section: Radial Nerve Fiber Size Distribution and Sproutingmentioning
confidence: 99%
“…This is an important observation given that some other trophic effects of neurotrophins, such as the propensity to regrow or extend peripheral dendrites, are seen only in damaged areas of the organ of Corti of deafened cochleae (Wise et al 2005(Wise et al , 2010. However, the effects observed may have been anticipated given known effects of neurotrophins upon neurons; neurotrophins are known to regulate ion channel expression and to modulate firing patterns and neuronal excitability throughout the central nervous system (Holm et al 1997;Lesser et al 1997;Kafitz et al 1999;Rose et al 2004;Davis-Lopez de Carrizosa et al 2009;Luther and Birren 2009).…”
Section: Discussionmentioning
confidence: 99%
“…168 It was considered that gene delivery via cochleostomy into the basal turn of the scala media was more effective than via RWM due to the existence of tight junctions between the scala tympani and scala media. 169 HSV, as a gene transfer vector is identified to be a promising carrier because of its ability to infect several cell types, including quiescent and proliferating cells. HSV with BDNF had successfully infected HCs and neurons, and this saved 94.7% of the original population of SGCs after aminoglycoside ototoxic injuries.…”
Section: Viral Mediated Bdnf Deliverymentioning
confidence: 99%